Factors Behind High Performance - Tuan, Luu Trong (Mediterranean Journal of Social Sciences, 2011)
According to Rogers (2005), the Bain analysis shows that only around 15% of companies actually have an organization thathelps them to outperform. In creating high-performance environment, leaders recognize three critical factors that determine and guide theirleadership responsibility. First, they must learn how to lead themselves before they can lead others successfully. Second, they are notactually delivering the vision themselves, but merely overseeing its delivery by the â€œrealâ€ performers in the organization. Third, leadersshould distinguish â€œleaderâ€ from â€œleadershipâ€. Not everyone can be a leader, but everyone in the organization can assume leadership roles.